DRD4 Mitigates Myocardial Ischemia/Reperfusion Injury in Association With PI3K/AKT Mediated Glucose Metabolism - Liu, Xue-song; Zeng, Jing; Yang, Yu-xue; Qi, Chun-lei; Xiong, Ting; Wu, Geng-ze; Zeng, Chun-yu; Wang, Da-xin (Frontiers in Pharmacology, 2021)
Ischemia-reperfusion (I/R) could cause heart irreversible damage, which is tightly combined with glucose metabolism disorder. It is demonstrated that GLUT4 (glucose transporter 4) translocation is critical for glucose metabolism in the cardiomyocytes under I/R injury. Moreover, DRD4 (dopamine receptor D4) modulate glucose metabolism, and protect neurocytes from anoxia/reoxygenation (A/R) injury. Thus, DRD4 might regulate myocardial I/R injury in association with GLUT4-mediated glucose metabolism. However, the effects and mechanisms are largely unknown. In the present study, the effect of DRD4 in heart I/R injury were studied ex vivo and in vitro. For I/R injury ex vivo, DRD4 agonist (PD168077) was perfused by Langendorff system in the isolated rat heart. DRD4 activated by PD168077 improved cardiac function in the I/R-injured heart as determined by the left ventricular developed pressure (LVDP), +dp/dt, and left ventricular end diastolic pressure (LVEDP), and reduced heart damage evidenced by infarct size, the release of troponin T (TNT) and lactate dehydrogenase (LDH). DRD4 activation diminished I/R injury induced apoptosis and enhanced cell viability impaired by I/R injury in cardiomyocyte, showed by TUNEL staining, flow cytometer and CCK8 assay. Furthermore, DRD4 activation did not change total GULT4 protein expression level but increased the membrane GULT4 localization determined by western blot. In terms of mechanism, DRD4 activation increased pPI3K/p-AKT but not the total PI3K/AKT during anoxia/reoxygenation (A/R) injury in vitro. Interestingly, PI3K inhibitor, Wortmannin, blocked PI3K/AKT pathway and depleted the membrane GULT4, and further promoted apoptosis showed by TUNEL staining, flow cytometer, western blot of cleaved caspase 3, BAX and BCL2 expression. Thus, DRD4 activation exerted a protective effect against I/R injury by promoting GLUT4 translocation depended on PI3K/AKT pathway, which enhanced the ability of glucose uptake, and ultimately reduced the apoptosis in cardiomyocytes.